Targeting inhibition of the inflammatory response: advances in the treatment of myocardial fibrosis with natural medicine and active ingredients - Shu, Chang; Ren, Chunzhen; Chen, Qilin; Wang, Yanyun; Li, Ruochen; Zhang, Yue; Yang, Shuyu; Wang, Ci; Li, Yingdong (Frontiers in Cardiovascular Medicine, 2025)
Myocardial fibrosis is a critical pathological foundation of cardiovascular diseases and a fundamental process underlying myocardial remodeling. The inflammatory response is a key driver of myocardial fibrosis, promoting the proliferation of myocardial fibroblasts and collagen deposition through the activation of multiple cytokines and signaling pathways. Natural medicines and active ingredients exhibit distinct therapeutic advantages characterized by not only potent pharmacological efficacy and favorable safety profiles, but also unique multi-target mechanisms of action that enable synergistic modulation of complex pathological pathways. These properties enable them to comprehensively modulate the inflammatory response, thereby providing novel therapeutic strategies for myocardial fibrosis. In this review, we explore the etiology of myocardial fibrosis and the mechanisms by which natural medicines and active ingredients inhibit the inflammatory response to treat myocardial fibrosis. We aim to provide a solid reference for future research on natural medicine-based therapies targeting the inflammatory pathways involved in myocardial fibrosis.